(untitled) (Bangladesh Journal of Botany, 2010)
Characterization of sixteen jute genotypes, from Corchorus olitorius L. and Corchorus capsularis L. using jute specific SSR marker attained a high polymorphism value of 92.20%. A total of 171 different alleles were amplified by 27 primer pairs with a mean of 6.33 ± 2.04 alleles per locus. The genetic diversity was also relatively high (0.81 ± 0.06). The Un-weighted Pair-group Method with Arithmetic averages (UPGMA) cluster analysis of the 16 jute genotypes produced a dendogram, which was in concordance with known information. The study reinforces the utility of SSR primers for providing useful and high levels of markers for individual plant genotypes even with a narrow genetic base. Key words: Jute; Genetic diversity; SSR; Genotypes; Polymorphism DOI: 10.3329/bjb.v38i2.5140 Bangladesh J. Bot. 38(2): 153-161, 2009 (December)